Here is the problem.

Let $f$ be the function that has the value of $f(1)=1$ and $f'(1)=2$. Find the value of $$ L = \lim_{x \to 1} {\frac{\arctan{\sqrt{f(x)}-\arctan{f(x)}}}{ \left (\arcsin{\sqrt{f(x)}}-\arcsin{f(x)}\right)^2}} $$

I have tried using $$ L=\lim_{x\to 1} \frac{1}{x-1}\frac{\frac{\arctan{\sqrt{f(x)}}-\arctan{\sqrt{f(1)}}}{x-1}-\frac{\arctan{{f(x)}}-\arctan{{f(1)}}}{x-1}} {\left [\frac{\arcsin{\sqrt{f(x)}}-\arcsin{\sqrt{f(1)}}}{x-1}-\frac{\arcsin{{f(x)}}-\arcsin{{f(1)}}}{x-1} \right ]^2} $$ and reduced that big chunks by using $f'(a)=\lim_{x \to a} \frac{f(x)-f(a)}{x-a}$ which I got $$ \begin{split} L&=\lim_{a\to 1} \frac{1}{a-1}\frac{\Big [ \arctan\sqrt{f(x)} \Big ]'_{x=a} - \Big [ \arctan{f(x)} \Big ]'_{x=a}} {\Big [ \arcsin\sqrt{f(x)} \Big ]'_{x=a} - \Big [ \arcsin{f(x)} \Big ]'_{x=a}}\\[2em] &=\lim_{a\to 1} \frac{1}{a-1} \frac{\frac{1}{1+f(a)}\frac{1}{2\sqrt{f(a)}}f'(a)-\frac{1}{1+(f(a))^2}f'(a)} {\left [ \frac{1}{\sqrt{1-f(a)}}\frac{1}{2\sqrt{f(a)}}f'(a)-\frac{1}{\sqrt{1-(f(a))^2}}f'(a) \right ]^2}\\[2em] &=\lim_{a\to 1} \frac{1}{f'(a)\frac{a-1}{1-f(a)}} \frac{\frac{1}{1+f(a)}\frac{1}{2\sqrt{f(a)}}-\frac{1}{1+(f(a))^2}} {\left [ \frac{1}{2\sqrt{f(a)}}-\frac{1}{\sqrt{1+f(a)}} \right ]^2}\\[2em] &=\lim_{a\to 1}{-\frac{\frac{1}{1+f(a)}\frac{1}{2\sqrt{f(a)}}-\frac{1}{1+(f(a))^2}} {\left [ \frac{1}{2\sqrt{f(a)}}-\frac{1}{\sqrt{1+f(a)}} \right ]^2}}\\[2em] &=\boxed{(\sqrt{2}+1)^2} \end{split} $$ but the answer keys tell me that the answer of this problem is $L=\left( \frac{\sqrt{2}+1}{2}\right)^2$. So, Can someone please explain to me what did I do wrong?

  • 1
    +1 for all the efforts you made – Deepesh Meena Sep 14 at 13:25
  • You could plug in f (x)=1+2(x-1) then use Wolfram Alpha to see if your answer is correct. – ericf Sep 14 at 14:27

There are several steps that are not clearly allowed.

The first step is okay: $$ \frac{ \arctan \sqrt{f(x)} - \arctan f(x) }{ \left( \arcsin \sqrt{f(x)} - \arcsin f(x) \right)^2 } = \frac{ (\arctan \sqrt{f(x)} - \arctan 1) - (\arctan f(x) - \arctan 1) }{ \left( (\arcsin \sqrt{f(x)} - \arcsin 1) - (\arcsin f(x) - \arcsin 1) \right)^2 } \\ = \frac{1}{x-1} \frac{ \frac{\arctan \sqrt{f(x)} - \arctan 1}{x-1} - \frac{\arctan f(x) - \arctan 1}{x-1} }{ \left( \frac{\arcsin \sqrt{f(x)} - \arcsin 1}{x-1} - \frac{\arcsin f(x) - \arcsin 1}{x-1} \right)^2 } \\ $$

Then you assume not only that the limit can be distributed over the internal terms, which would give derivatives at $x=1$, e.g. $\left[ \arctan\sqrt{f(x)} \right]'_{x=1},$ but even that you can take the limits of the derivatives, $\lim_{a \to 0} \left[ \arctan\sqrt{f(x)} \right]'_{x=a}.$

Also, as gimusi has already pointed out, $\arcsin \sqrt{f(x)}$ and $\arcsin f(x)$ are not differentiable when $f(x)=1.$

  • Thanks for the quote! – gimusi Sep 14 at 23:36

Probably the derivation is wrong because arcsin x is not differentiable at $x=1$, therefore your first step is not allowed.

As an alternative, since $f(x)$ is continuos at $x=1$ we have that

$$L = \lim_{y \to 1^-} {\frac{\arctan{\sqrt{y}-\arctan{y}}}{ \left (\arcsin{\sqrt{y}}-\arcsin{y}\right)^2}}$$

then we can use that

  • $\arcsin(x) = \arctan\left(\frac{x}{\sqrt{1 - x^2}}\right)$
  • $\arctan(u) - \arctan(v) = \arctan\left(\frac{u - v}{1 + uv}\right) $

to obtain

$$L = \lim_{y \to 1^-} \frac{ \arctan\left( \frac{\sqrt y -y}{1+y\sqrt y}\right)} { \left[\arctan \left(\frac{\sqrt y \sqrt{1-y^2}-y\sqrt{1-y}} { \sqrt{(1-y)(1-y^2)}+y\sqrt y} \right)\right]^2 }=\frac{3+ 2\sqrt 2}{4}=\left( \frac{\sqrt{2}+1}{2}\right)^2$$

indeed by $y=1-u$ with $u\to 0^+$ by binomial expansion $\sqrt y = 1-\frac12 u +o(u)$ it easy to show that

  • $\arctan\left( \frac{\sqrt y -y}{1+y\sqrt y}\right)\sim \frac 14 u$
  • $\arctan \left(\frac{\sqrt y \sqrt{1-y^2}-y\sqrt{1-y}} { \sqrt{(1-y)(1-y^2)}+y\sqrt y} \right)\sim (\sqrt 2 -1) \sqrt u$

and therefore

$$\frac{ \arctan\left( \frac{\sqrt y -y}{1+y\sqrt y}\right)} { \left[\arctan \left(\frac{\sqrt y \sqrt{1-y^2}-y\sqrt{1-y}} { \sqrt{(1-y)(1-y^2)}+y\sqrt y} \right)\right]^2 }\sim \frac{\frac 14 u}{(\sqrt 2 -1)^2 u}=\frac{3+ 2\sqrt 2}{4}$$

  • I think it is "differentiable" instead of "derivable". But good answer nevertheless! (+1) – Math_QED Sep 15 at 11:05
  • 1
    Thanks I fix that! Bye – gimusi Sep 15 at 11:06

We shall need several times the following principle: If $f(0)=0$, $\>f'(0)=1$, and $\lim_{x\to0} g(x)=0$, then we may write $$f\bigl(g(x)\bigr)=g(x)\>h(x)\ ,\tag{1}$$ whereby the function $x\mapsto h(x)$ defined by $(1)$ satisfies $\lim_{x\to0}h(x)=1$.

We only need that $f(x)\nearrow1$ when $x\nearrow 1$ (note that your expression is undefined when $x>1$). There are functions $x\mapsto \alpha:=\alpha(x)$ and $x\mapsto\beta:=\beta(x)$ with $$0<\alpha<\beta\>,\qquad \lim_{x\to1-}\alpha(x)=\lim_{x\to1-}\beta(x)=0\ ,$$ such that $$\sqrt{f(x)}=\cos\alpha\>,\qquad f(x)=\cos\beta\ .$$ This ensures $$\arcsin\sqrt{f(x)}-\arcsin f(x)=\beta-\alpha\ .$$ On the other hand $$\arctan\sqrt{f(x)}-\arctan f(x)=\arctan{\cos\alpha-\cos\beta\over 1+\cos\alpha\cos\beta}={1\over2}(\cos\alpha-\cos\beta)\> g(x)\>,$$ whereby $\lim_{x\to1-}g(x)=1$. Now $${1\over2}(\cos\alpha-\cos\beta)=\sin{\beta+\alpha\over2}\sin{\beta-\alpha\over2}={1\over4}(\beta+\alpha)(\beta-\alpha) h(x)\ ,$$ whereby $\lim_{x\to1-} h(x)=1$. It follows that $$L={1\over4}\lim_{x\to1-}{\beta+\alpha\over\beta-\alpha }={1\over4}\lim_{x\to1-}{1+{\alpha\over\beta}\over1-{\alpha\over\beta}}.$$ As $\cos^2\alpha=\cos\beta$ for all $x<1$ we have $\>\sin^2\alpha=2\sin^2{\beta\over2}$, which then leads to $\lim_{x\to1-}{\alpha\over\beta}={1\over\sqrt{2}}$, so that we end up with $$L={1\over4}\bigl(3+2\sqrt{2}\bigr)\ .$$

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.